Prescribing trends over time by non-medical independent prescribers in primary care settings across Wales (2011–2018): a secondary database analysis. Issue 10 (13th October 2020) - Alghamdi, Saeed Saad A; Hodson, Karen; Deslandes, Paul; Gillespie, David; Haines, Kath; Hulme, Elliott; Courtenay, Molly; Deslandes, Rhian
Abstract : Introduction: As of 2015, as part of the implementation of the Welsh Government primary care plan and primary care clusters, the Welsh Government has encouraged non-medical healthcare professionals working in primary care to train as independent prescribers (IPs). Objectives: This research aimed to identify the number of NMIPs in primary care in Wales and describe their prescribing trend of items between 2011 and 2018, in order to compare their prescribing pattern before and after the implementation of primary care clusters for Wales. Design: Retrospective secondary data analysis and interrupted time series analysis in order to compare prescribing by non-medical independent prescribers (NMIPs) preimplementation and postimplementation of primary care clusters across Wales. Results: Over the study period, 600 NMIPs (nurses n=474 and pharmacists n=104) had prescribed at least one item. The number of nurse IPs increased by 108% and pharmacists by 325% (pharmacists had the largest increase between July 2015 and March 2018). The number of items prescribed by NMIPs increased over time by an average of 1380 per month (95% CI 904 to 1855, p<0.001) after the implementation of primary care clusters compared with 496 (95% CI 445 to 548, p<0.001) prior its implementation. Approximately one-third of the items prescribed by NMIPs was within Betsi Cadwaladr University Health Board (HB) with only 4% in Powys Teaching HB. Conclusion: The number of NMIPs and their volume of prescribing in primary care in Wales has increased following the implementation of primary care clusters in 2015. This suggests that the Government's recommendations of using NMIPs in primary care have been implemented. Future studies should focus on efficiency and quality of prescribing by NMIPs in primary care.